A battery separator and method of making the same
Patent Information
- Application Number
- CN202611156236.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
然而,由于聚乙烯(PE)隔膜和聚丙烯(PP)隔膜的固有特性,其熔点(Tm)仅为135℃和165℃左右,在过热条件下会发生严重的热收缩,不仅存在高温应用的局限性,还会造成内部短路和潜在的爆炸危险
[0029]本发明选用具有非对称结构的二胺单体与芳香族或杂芳香族的二甲酰氯进行共聚,从分子层面构建了兼具平面性及适度无序性的特种聚酰胺大分子链,以这种特定的聚酰胺聚合物作为原料制备的聚酰胺纤维膜作为基体,与无机固态电解质纳米颗粒复合形成电池隔膜。本发明的隔膜不仅在高温条件下具有优良的尺寸稳定性和抗刺穿能力,有效提升了电池的安全性,而且其聚酰胺纤维膜基体具有更适宜的三维互联多孔结构,有利于电解液的浸润和锂离子的快速传输,也为无机固态电解质纳米颗粒提供了良好的分散与复合界面,能够与无机固态电解质纳米颗粒更好地配合,使隔膜在具有优良的耐高温性能的同时具备较高的离子电导率,大大提高电池的安全性和电化学性能。
Smart Images

Figure CN123018349A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery separator technology, and in particular to a battery separator and its preparation method. Background Technology
[0002] Lithium-ion batteries, with their advantages of high operating voltage, strong current discharge capability, and environmental friendliness, are widely used in portable electronic devices and electric vehicles. The separator is an indispensable component of a lithium-ion battery system; it prevents short circuits between the positive and negative electrodes, ensuring battery safety, while providing an effective channel for the rapid migration of lithium ions. Currently, polyolefin microporous membranes are widely used in the lithium-ion battery industry due to their good chemical stability and mechanical strength. However, due to the inherent characteristics of polyethylene (PE) and polypropylene (PP) separators, their melting points (Tm) are only around 135℃ and 165℃, respectively. Under overheating conditions, they undergo severe thermal shrinkage, limiting their application in high temperatures and potentially causing internal short circuits and explosion hazards. Ceramic coating modification is a common method to improve the heat resistance of polyolefin separators; however, when ceramic particles are coated on polyolefin microporous membranes, they can clog pores or reduce porosity, decreasing ion conductivity and ultimately reducing battery power density and other performance characteristics. Polyamide materials exhibit excellent heat resistance (Tm>400℃) due to the strong hydrogen bonding between their macromolecular chains. However, their poor adhesion to PP or PE substrates as coating materials significantly reduces their temperature resistance. Therefore, developing battery separators that combine good high-temperature resistance with high ionic conductivity is of great significance for applications. Summary of the Invention
[0003] Based on the technical problems existing in the background technology, the present invention proposes a battery separator and its preparation method. The separator has good heat resistance and high ionic conductivity, which can greatly improve the electrochemical performance and safety of the battery.
[0004] This invention proposes a battery separator, which includes a polyamide fiber membrane matrix and inorganic solid electrolyte nanoparticles uniformly distributed in the polyamide fiber membrane matrix.
[0005] The polyamide fiber membrane matrix comprises a polyamide polymer, which is obtained by polymerizing a diamine monomer and a diformyl chloride monomer; the diamine monomer includes at least one of the compounds shown in Formula I; the diformyl chloride monomer includes at least one of aromatic diformyl chloride and heteroaromatic diformyl chloride.
[0006]
[0007] Formula I;
[0008] In Formula I, A and B are each independently selected from any one of phenylene, imidazolyl, imidazolyl, imidazolyl, furanyl, imidaphenyl, benzothiazolyl, benzoxazolyl, imidazolyl, and benzofuranyl, and A and B are different.
[0009] This invention synthesizes inorganic solid electrolyte nanoparticles into a polyamide fiber membrane matrix synthesized from specific monomers to obtain a battery separator. The rigid inorganic solid electrolyte nanoparticles act as physical crosslinking points throughout the system, forming a crosslinked network that significantly improves ionic conductivity and enhances the separator's mechanical strength and high-temperature shrinkage resistance. By copolymerizing a diamine monomer with an asymmetric structure with aromatic or heteroaromatic diformyl chloride, a special polyamide macromolecular chain with both planarity and moderate disorder is constructed at the molecular level. The resulting polyamide polymer retains the rigidity and high heat resistance of the aromatic or heteroaromatic rings, thus exhibiting extremely high glass transition temperature, thermal decomposition temperature, and modulus. This results in excellent dimensional stability and puncture resistance of the separator under high-temperature conditions, effectively improving battery safety. On the one hand, this asymmetric structure design breaks the overly regular arrangement of molecular chains, which can inhibit excessive crystallization, improve the solubility and film-forming properties of polymers, make the spinning solution more stable, and form fibers with more uniform diameter and more stable size, which is conducive to reducing the shrinkage rate of the separator at high temperatures. On the other hand, it can create gaps between molecular chains, in which solvent molecules can occupy space, which is conducive to the formation of a porous structure. This results in the prepared polyamide fiber membrane having a more suitable three-dimensional interconnected porous structure, which is conducive to electrolyte wetting and rapid lithium ion transport. It also provides a good dispersion and composite interface for inorganic solid electrolyte nanoparticles, which can better cooperate with inorganic solid electrolyte nanoparticles. This allows the prepared separator to have excellent high temperature resistance and high ionic conductivity, greatly improving the safety and electrochemical performance of the battery.
[0010] Preferably, the diamine monomer comprises at least one of 2-(4-aminophenyl)-1,3-benzothiazole-5-amine (CAS No. 13676-50-1), 5-amino-2-(4-aminophenyl)benzoxazole (CAS No. 13676-47-6), 5-amino-2-(4-aminophenyl)benzofuran (CAS No. 84102-58-9), 5-amino-2-(4-aminophenyl)benzimidazole (CAS No. 7621-86-5), and 5-(4-aminophenyl)thiazole-2-amine (CAS No. 90349-87-4).
[0011] Preferably, the dicarboxylic chloride monomer includes at least one selected from terephthaloyl chloride, isophthaloyl chloride, 4,4'-biphenyl dicarboxylic chloride, 2,6-pyridine dicarboxylic chloride, 2,5-thiophene dicarboxylic chloride, and 2,5-furan dicarboxylic chloride.
[0012] In this invention, by selecting the specific diamine monomer and diformyl chloride monomer mentioned above, the polymerization reaction is highly efficient, and the prepared polyamide fiber membrane has excellent thermal stability and mechanical strength, and good overall performance.
[0013] Preferably, the molar ratio of the diamine monomer to the diformyl chloride monomer is 1 to 1.5:1. By controlling the appropriate molar ratio of the diamine monomer to the diformyl chloride monomer, the efficiency of the polymerization reaction can be improved.
[0014] This invention does not impose any special restrictions on the type of inorganic solid electrolyte nanoparticles; conventional inorganic solid electrolyte nanoparticles used in the battery field can be employed. Preferably, the inorganic solid electrolyte nanoparticles are selected from at least one of garnet-type solid electrolyte nanoparticles, perovskite-type solid electrolyte nanoparticles, and NASICON-type solid electrolyte nanoparticles.
[0015] Preferably, the inorganic solid electrolyte nanoparticles are selected from at least one of lithium aluminum titanium phosphate (LATP) nanoparticles, lithium lanthanum zirconium oxide (LLZO) nanoparticles, and lithium lanthanum zirconium tantalum oxide (LLZTO) nanoparticles.
[0016] Preferably, the particle size D50 of the inorganic solid electrolyte nanoparticles is 200~1000nm, more preferably 400~600nm. In this invention, by controlling the particle size of the inorganic solid electrolyte nanoparticles, a cross-linked network supported by a particle skeleton can be formed, which is beneficial for forming continuous lithium-ion transport channels, further improving the conductivity of the separator, reducing impedance, and simultaneously improving the mechanical strength and high-temperature shrinkage resistance of the separator.
[0017] Preferably, the mass ratio of the inorganic solid electrolyte nanoparticles to the polyamide polymer is 0.2~0.4:1. By controlling the appropriate mass ratio of inorganic solid electrolyte nanoparticles to polyamide polymer, continuous conduction channels can be constructed while avoiding the decrease in ionic conductivity caused by pore blockage, which is beneficial to improving the ionic conductivity of the membrane.
[0018] Preferably, the polyamide fiber membrane has a fiber diameter of 100-2000 nm, more preferably 100-1000 nm. By controlling the appropriate fiber diameter of the polyamide fiber membrane, dense physical cross-linking points can be formed, greatly improving the puncture resistance and high-temperature shrinkage resistance of the membrane. At the same time, the fibers have a suitable pore size, avoiding the decrease in ionic conductivity caused by pore blockage. Thus, the membrane has excellent strength, high-temperature resistance, and ionic conductivity.
[0019] Preferably, the preparation method of the polyamide polymer includes: adding diamine monomer and diformyl chloride monomer to an organic solvent containing a catalyst, performing a pre-condensation reaction at -10~0℃ for 50~100 min under an inert atmosphere, then successively raising the temperature to 25~35℃ and holding the reaction for 30~50 min, raising the temperature to 50~70℃ and holding the reaction for 80~100 min, raising the temperature to 85~95℃ and holding the reaction for 100~150 min.
[0020] Preferably, the preparation method of the polyamide polymer includes: adding diamine monomer and diformyl chloride monomer to an organic solvent containing a catalyst, performing a pre-condensation reaction at -10~0℃ for 50~100 min under an inert atmosphere, then sequentially heating to 25~35℃ at a heating rate of 1.5~2.5℃ / min and holding the temperature for 30~50 min, heating to 50~70℃ at a heating rate of 1~2℃ / min and holding the temperature for 80~100 min, and heating to 85~95℃ at a heating rate of 0.5~1.5℃ / min and holding the temperature for 100~150 min.
[0021] Preferably, the catalyst comprises a Lewis acid catalyst and a nucleophilic catalyst, wherein the mass ratio of the Lewis acid catalyst to the nucleophilic catalyst is 1:0.1~0.4; the Lewis acid catalyst is selected from lithium chloride or calcium chloride, and the nucleophilic catalyst is selected from 4-dimethylaminopyridine, 4-pyrrolylpyridine or N-methylimidazole.
[0022] Preferably, the organic solvent includes a main solvent and a co-solvent, and the volume ratio of the main solvent to the co-solvent is 2 to 4:1; the main solvent is selected from N-methylpyrrolidone or dimethylacetamide, and the co-solvent is selected from 1-butyl-3-methylimidazolium tetrafluoroborate or 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0023] This invention optimizes the preparation method of polyamide polymers, including using programmed temperature rise to reduce side reactions, using a composite organic solvent system to effectively dissolve the high-rigidity polyamide macromolecular chains, and using a composite catalyst system for synergistic catalysis, thereby obtaining polyamide products with high molecular weight and narrow molecular weight distribution, and thus preparing membranes with excellent thermal performance.
[0024] Preferably, the sum of the masses of the diamine monomer and the diformyl chloride monomer is equivalent to 5% to 20% of the mass of the organic solvent.
[0025] Preferably, the mass of the catalyst is equivalent to 0.5% to 3% of the mass of the organic solvent.
[0026] The present invention also proposes a method for preparing the battery separator, comprising: adding the inorganic solid electrolyte nanoparticles to a spinning solution containing the polyamide polymer, dispersing them evenly, and then performing electrospinning to obtain the separator.
[0027] Preferably, the electrospinning parameters include: a spinning voltage of 10~50kV and a distance of 5~30cm between the spinneret and the collector. By controlling the electrospinning parameters, a more uniform fiber structure can be formed, which is beneficial to improving the mechanical strength, thermal stability, and ionic conductivity of the diaphragm.
[0028] The beneficial effects of this invention are as follows:
[0029] This invention uses a diamine monomer with an asymmetric structure to copolymerize with aromatic or heteroaromatic diformyl chloride, constructing a special polyamide macromolecular chain with both planarity and moderate disorder at the molecular level. A polyamide fiber membrane prepared using this specific polyamide polymer is then used as the matrix, which is composited with inorganic solid electrolyte nanoparticles to form a battery separator. The separator of this invention not only exhibits excellent dimensional stability and puncture resistance under high-temperature conditions, effectively improving battery safety, but its polyamide fiber membrane matrix also possesses a more suitable three-dimensional interconnected porous structure, which is beneficial for electrolyte wetting and rapid lithium-ion transport. It also provides a good dispersion and composite interface for the inorganic solid electrolyte nanoparticles, enabling better integration with them. This allows the separator to possess both excellent high-temperature resistance and high ionic conductivity, significantly improving battery safety and electrochemical performance.
[0030] Furthermore, this invention optimizes the preparation method of polyamide polymers, including using programmed temperature rise to reduce side reactions, using a composite organic solvent system to effectively dissolve the high-rigidity polyamide macromolecular chains, and using a composite catalyst system for synergistic catalysis. The resulting polyamide polymer has a high molecular weight and a narrow molecular weight distribution, and the prepared spun fibers have a more uniform diameter and better heat resistance of the separator, thereby further improving the safety and electrochemical performance of the battery. Attached Figure Description
[0031] Figure 1 The DCR test results are shown for the separators of the examples and comparative examples, which were respectively assembled into 3Ah pouch cells. Detailed Implementation
[0032] The technical solution of the present invention will now be described in detail through specific embodiments.
[0033] Example 1
[0034] Preparation of polyamide polymers:
[0035] 35g of N-methylpyrrolidone (NMP) was mixed with 15g of 1-butyl-3-methylimidazolium tetrafluoroborate to obtain an organic solvent; 0.25g of 4-dimethylaminopyridine and 1g of lithium chloride were dissolved in the above organic solvent, and then 2.4g of 2-(4-aminophenyl)-1,3-benzothiazol-5-amine was added and dissolved completely. Nitrogen gas was then introduced for protection. The mixture was cooled to -10°C, and 2.0 g of terephthaloyl chloride was slowly added at -10°C. The temperature was then raised to -5~0°C and maintained for 60 min. The temperature was then raised to 30°C at a rate of 2°C / min and maintained for 40 min. The temperature was then raised to 60°C at a rate of 1.5°C / min and maintained for 90 min. The temperature was then raised to 90°C at a rate of 1°C / min and maintained for 120 min. During the reaction, triethylamine was slowly added dropwise through a constant-pressure dropping funnel, causing the hydrogen chloride byproduct to form a complex with the triethylamine. This complex was then collected and recovered using a condensation system. After the reaction was completed, the resulting reaction product was filtered through a 0.5 μm polytetrafluoroethylene microporous membrane at a pressure of 0.2 MPa to obtain a spinning solution containing polyamide polymer.
[0036] Preparation of battery separator:
[0037] 1g of LATP nanoparticles with a particle size D50 of 500nm were added to the spinning solution containing polyamide polymer prepared above, and stirred for 2h until uniformly dispersed. Then, the solution was added to a 10mL syringe and electrospun using an electrospinning apparatus with a voltage of 12kV. The distance between the spinneret and the collector was 15cm, resulting in a battery separator with a thickness of 12µm. The battery separator consists of a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 100~500nm.
[0038] Preparation of positive electrode:
[0039] PVDF (polyvinylidene fluoride) binder was dissolved in NMP (N-methylpyrrolidone) solvent and stirred until completely dissolved. Then, conductive carbon nanotubes were added and stirred until homogeneous. Finally, NCM622 ternary cathode material was added and stirred until homogeneous to obtain a cathode slurry. The mass ratio of PVDF binder, conductive agent, and NCM622 ternary cathode material was 2:3:95. The cathode slurry was uniformly coated on both surfaces of aluminum foil and dried in a vacuum oven at 100℃ to remove the NMP solvent. Then, it was compacted using a roller mill, with the compaction density controlled at 3.5 g / cm³. 3 The surface density of a single side is controlled at 150g / m². 2 The positive electrode sheet is obtained by cutting.
[0040] Preparation of negative electrode:
[0041] CMC (sodium carboxymethyl cellulose) was dissolved in deionized water and stirred until completely dissolved. Acetylene black and graphite powder were added as conductive agents and stirred thoroughly. Finally, SBR (styrene-butadiene rubber) emulsion was added and stirred evenly to obtain the negative electrode slurry. The mass ratio of graphite powder, acetylene black, CMC, and SBR was 95:2:1.5:1.5. The negative electrode slurry was uniformly coated onto both surfaces of a copper foil and dried in a vacuum oven at 100℃ to remove NMP solvent. It was then compacted using a roller mill, with the compaction density controlled at 1.6 g / cm³ and the single-sided areal density controlled at 150~200 g / m². The foil was then slit to obtain the negative electrode sheet.
[0042] Assemble the battery:
[0043] After the prepared separator is cut, the positive electrode, separator and negative electrode are stacked in sequence to form a core. In a dry environment (dew point ≤ -40℃), the electrolyte of Jiangsu Tinci High-Tech Materials Co., Ltd., brand name TC-EGX09-E8A2, is injected. Then, it is left to stand at 45℃ for 24 hours to allow the electrolyte to fully wet the electrode and separator. After formation and capacity testing, a 3Ah soft pack battery is obtained.
[0044] Example 2
[0045] The only difference between Example 2 and Example 1 is that in the preparation of the polyamide polymer, 2-(4-aminophenyl)-1,3-benzothiazole-5-amine is replaced with an equimolar amount of 5-amino-2-(4-aminophenyl)benzoxazole, while other conditions remain unchanged.
[0046] The battery separator prepared above includes a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 300~600nm.
[0047] Example 3
[0048] The only difference between Example 3 and Example 1 is that in the preparation of the battery separator, LATP nanoparticles are replaced with an equal mass of LLZO particles with a particle size D50 of 500 nm, while other conditions remain unchanged.
[0049] The battery separator prepared above includes a polyamide fiber membrane matrix and LLZO nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 200~500nm.
[0050] Example 4
[0051] The only difference between Example 4 and Example 1 is the preparation method of the polyamide polymer; all other conditions remain the same. The specific preparation method of the polyamide polymer is as follows:
[0052] 1.25 g of lithium chloride was dissolved in 50 g of N-methylpyrrolidone (NMP), and then 2.4 g of 2-(4-aminophenyl)-1,3-benzothiazole-5-amine was added and dissolved completely. Nitrogen gas was then introduced for protection, and the mixture was cooled to -10 °C. 2.0 g of terephthaloyl chloride was slowly added at -10 °C, and the temperature was raised to -5 to 0 °C and maintained for 60 min. The temperature was then increased to 60 °C at a rate of 2 °C / min and maintained for 6 h. During the reaction, triethylamine was slowly added dropwise through a constant-pressure dropping funnel, allowing the byproduct hydrogen chloride to form a complex with the triethylamine. This complex was collected and recovered using a condenser system. After the reaction was complete, the resulting reaction product was filtered through a 0.5 μm polytetrafluoroethylene microporous membrane at a pressure of 0.2 MPa to obtain a spinning solution containing polyamide polymer.
[0053] The battery separator prepared above includes a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 200~1500nm.
[0054] Example 5
[0055] Preparation of polyamide polymers:
[0056] 40g of dimethylacetamide was mixed with 20g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt to obtain an organic solvent; 0.1g of... 4-Dimethylaminopyridine and 1g of calcium chloride were dissolved in the above organic solvent, and then 2.4g of 2-(4-aminophenyl)-1,3-benzothiazole-5-amine was added and dissolved completely. Nitrogen gas was then introduced for protection, and the mixture was cooled to -10°C. At -10°C, 2.0g of terephthaloyl chloride was slowly added, and the temperature was raised to -5~0°C and maintained for 50 min. The temperature was then increased to 25°C at a rate of 1.5°C / min and maintained for 30 min. The temperature was then increased to 50°C at a rate of 1°C / min and maintained for 80 min. Finally, the temperature was increased to 85°C at a rate of 0.5°C / min and maintained for 100 min. During the reaction, triethylamine was slowly added dropwise through a constant-pressure dropping funnel, causing the byproduct hydrogen chloride to form a complex with the triethylamine. This complex was collected and recovered using a condenser system. After the reaction was complete, the resulting reaction product was filtered through a 0.5μm polytetrafluoroethylene microporous membrane at 0.2 μm. Filtration under MPa pressure yields a spinning solution containing polyamide polymer.
[0057] Preparation of battery separator:
[0058] 1g of LATP nanoparticles with a particle size D50 of 500nm were added to the spinning solution containing polyamide polymer prepared above, and stirred for 2h until uniformly dispersed. Then, the solution was added to a 10mL syringe and electrospun using an electrospinning apparatus with a voltage of 12kV. The distance between the spinneret and the collector was 15cm, resulting in a battery separator with a thickness of 12µm. The battery separator consists of a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 300~700nm.
[0059] The assembly method of the positive electrode, negative electrode and battery is the same as in Example 1.
[0060] Example 6
[0061] Preparation of polyamide polymers:
[0062] 40g of N-methylpyrrolidone (NMP) was mixed with 10g of 1-butyl-3-methylimidazolium tetrafluoroborate to obtain an organic solvent; 0.2g of N-methylimidazolium and 0.5g of lithium chloride were dissolved in the above organic solvent, and then 4.8g of [unspecified substance] was added. 2-(4-aminophenyl)-1,3-benzothiazole-5-amine was fully dissolved, then protected with nitrogen gas and cooled to -10°C. 4.0 g of terephthaloyl chloride was slowly added at -10°C, followed by heating to -5~0°C and holding for 100 min. The temperature was then increased to 35°C at a rate of 2.5°C / min and held for 50 min. The temperature was then increased to 70°C at a rate of 2°C / min and held for 100 min. Finally, the temperature was increased to 95°C at a rate of 1.5°C / min and held for 150 min. During the reaction, triethylamine was slowly added dropwise through a constant-pressure dropping funnel, causing the byproduct hydrogen chloride to form a complex with the triethylamine. This complex was collected and recovered using a condenser system. After the reaction, the resulting product was filtered through a 0.5 μm polytetrafluoroethylene microporous membrane at 0.2 MPa pressure to obtain a spinning solution containing polyamide polymer.
[0063] Preparation of battery separator:
[0064] 2g of LATP nanoparticles with a particle size D50 of 200nm were added to the spinning solution containing polyamide polymer prepared above, and stirred for 2h until uniformly dispersed. Then, the solution was added to a 10mL syringe and electrospun using an electrospinning apparatus with a voltage of 12kV. The distance between the spinneret and the collector was 15cm, resulting in a battery separator with a thickness of 12µm. The battery separator consists of a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 500~1000nm.
[0065] The assembly method of the positive electrode, negative electrode and battery is the same as in Example 1.
[0066] Comparative Example 1
[0067] Comparative Example 1 uses a commercially available 9µm PE + 3µm alumina diaphragm, model Enjie HS9T30.
[0068] Comparative Example 2
[0069] The only difference between Comparative Example 2 and Example 1 is that in the preparation of the polyamide polymer, 2-(4-aminophenyl)-1,3-benzothiazole-5-amine was replaced with an equimolar amount of p-phenylenediamine, while other conditions remained unchanged.
[0070] The battery separator prepared above includes a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 200~600nm.
[0071] Comparative Example 3
[0072] The only difference between Comparative Example 3 and Example 1 is that in the preparation of the polyamide polymer, 2-(4-aminophenyl)-1,3-benzothiazole-5-amine was replaced with an equimolar amount of 4,4'-diaminobiphenyl, while other conditions remained unchanged.
[0073] The battery separator prepared above includes a polyamide fiber membrane matrix and LATP nanoparticles uniformly distributed in the polyamide fiber membrane matrix, wherein the fiber diameter of the polyamide fiber membrane is 1~2μm.
[0074] Test case
[0075] The performance of the membranes prepared in the test examples and comparative examples was determined using the following methods:
[0076] The test methods for heat shrinkage rate and membrane ionic conductivity are in accordance with standard GB / T 36363-2018 "Polyolefin Separators for Lithium-ion Batteries".
[0077] DCR test method: (1) After the battery is fully charged at 25°C with constant current and constant voltage at 1C, it is left to stand at the ambient temperature to be tested for 8 hours. Then, it is discharged at 1C constant current to 2.0V. The discharge capacity at this temperature is recorded and used as the reference capacity Qt for the next pulse test. (2) After the battery is fully charged at 25°C with constant current and constant voltage at 1C, it is left to stand at the ambient temperature to be tested for 8 hours. Then, it is discharged at 1C constant current to 1 / 10*Qt capacity and left to stand for 1 hour. Then, it is discharged with 3Qt for 10 seconds, left to stand for 40 seconds, charged with 2.25Qt for 10 seconds, discharged at 1C constant current, and the DOD (depth of discharge) is adjusted to 20%. Then, it is left to stand for 1 hour. This process is repeated until the 9th 1 / 10*Qt capacity is discharged, and the pulse charge and discharge performance under different DOD is tested. Finally, it is discharged at 1C constant current to 2.0V, and the DOD is corrected with the actual discharge capacity. The DC internal resistance under different DOD is calculated.
[0078] The test results are shown in Table 1 and Figure 1 As shown:
[0079] Table 1
[0080]
[0081] From Table 1 and Figure 1 The data shows that:
[0082] Comparing Examples 1-4 with Comparative Examples 1-3, it can be seen that the separator prepared by this invention has the characteristics of low thermal shrinkage, high ionic conductivity, and good heat resistance. It can effectively prevent electrode contact at high temperatures, improve the safety of lithium batteries, reduce the resistance to lithium-ion migration, facilitate lithium-ion transport, and reduce battery impedance. This is because the present invention breaks the excessively regular arrangement of molecular chains through asymmetric monomer design, giving the polyamide fiber membrane matrix a more suitable three-dimensional interconnected porous structure. This not only facilitates electrolyte wetting and rapid lithium-ion transport but also provides a good dispersion and composite interface for inorganic solid electrolyte nanoparticles, resulting in better synergistic effects and effectively reducing impedance.
[0083] Comparing Examples 1-4, it can be seen that Examples 1-3, by optimizing the polyamide polymer preparation method, including using programmed temperature rise, a composite organic solvent system, and a composite catalyst system, can further improve the mechanical strength, thermal stability, and ionic conductivity of the diaphragm compared to the conventional polyamide polymer preparation method used in Example 4. This is because the polyamide polymer obtained by the above-mentioned specific preparation method has a high molecular weight and a narrow molecular weight distribution, and the resulting spun fibers have a more uniform diameter, thereby further improving the heat resistance, mechanical properties, and electrochemical properties of the diaphragm.
[0084] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A battery separator, characterized in that, The battery separator comprises a polyamide fiber membrane matrix and inorganic solid electrolyte nanoparticles uniformly distributed in the polyamide fiber membrane matrix; The polyamide fiber membrane matrix comprises a polyamide polymer, which is obtained by polymerizing a diamine monomer and a diformyl chloride monomer; the diamine monomer includes at least one of the compounds shown in Formula I; the diformyl chloride monomer includes at least one of aromatic diformyl chloride and heteroaromatic diformyl chloride. Formula I; In Formula I, A and B are each independently selected from any one of phenylene, imidazolyl, imidazolyl, imidazolyl, furanyl, imidaphenyl, benzothiazolyl, benzoxazolyl, imidazolyl, and benzofuranyl, and A and B are different.
2. The battery separator according to claim 1, characterized in that, The diamine monomer includes at least one of 2-(4-aminophenyl)-1,3-benzothiazole-5-amine, 5-amino-2-(4-aminophenyl)benzoxazole, 5-amino-2-(4-aminophenyl)benzofuran, 5-amino-2-(4-aminophenyl)benzimidazole, and 5-(4-aminophenyl)thiazole-2-amine.
3. The battery separator according to claim 1, characterized in that, The dicarboxylic chloride monomer includes at least one of terephthaloyl chloride, isophthaloyl chloride, 4,4'-biphenyl dicarboxylic chloride, 2,6-pyridine dicarboxylic chloride, 2,5-thiophene dicarboxylic chloride, and 2,5-furan dicarboxylic chloride.
4. The battery separator according to claim 1, characterized in that, The inorganic solid electrolyte nanoparticles are selected from at least one of garnet-type solid electrolyte nanoparticles, perovskite-type solid electrolyte nanoparticles, and NASICON-type solid electrolyte nanoparticles.
5. The battery separator according to claim 1, characterized in that, The mass ratio of the inorganic solid electrolyte nanoparticles to the polyamide polymer is 0.2~0.4:
1.
6. The battery separator according to claim 1, characterized in that, The polyamide fiber membrane has a fiber diameter of 100~1000nm.
7. The battery separator according to claim 1, characterized in that, The preparation method of the polyamide polymer includes: adding diamine monomer and diformyl chloride monomer to an organic solvent containing a catalyst, performing a pre-condensation reaction at -10~0℃ for 50~100 min under an inert atmosphere, then successively heating to 25~35℃ at a heating rate of 1.5~2.5℃ / min, holding the temperature for 30~50 min, heating to 50~70℃ at a heating rate of 1~2℃ / min, holding the temperature for 80~100 min, and heating to 85~95℃ at a heating rate of 0.5~1.5℃ / min, holding the temperature for 100~150 min.
8. The battery separator according to claim 7, characterized in that, The catalyst comprises a Lewis acid catalyst and a nucleophilic catalyst, wherein the mass ratio of the Lewis acid catalyst to the nucleophilic catalyst is 1:0.1~0.4; the Lewis acid catalyst is selected from lithium chloride or calcium chloride, and the nucleophilic catalyst is selected from 4-dimethylaminopyridine, 4-pyrrolidinylpyridine or N-methylimidazolium; The organic solvent includes a main solvent and a co-solvent, and the volume ratio of the main solvent to the co-solvent is 2~4:
1. The main solvent is selected from N-methylpyrrolidone or dimethylacetamide, and the co-solvent is selected from 1-butyl-3-methylimidazolium tetrafluoroborate or 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
9. A method for preparing a battery separator as described in any one of claims 1 to 8, characterized in that, The inorganic solid electrolyte nanoparticles are added to a spinning solution containing the polyamide polymer, dispersed evenly, and then electrospinned to obtain the final product.
10. The method for preparing the battery separator according to claim 7, characterized in that, The parameters of the electrospinning include: spinning voltage of 10~50kV and distance between the spinneret and the collector of 5~30cm.
